Activation cross section measurement of the (n,2n) reactions on natural Ir isotopes - Chasapoglou, S.; Kalamara, A.; Krokidi, K.; Michalopoulou, V.; Michalopoulou, V.; Stamatopoulos, A.; Vlastou, R.; Axiotis, M.; Lagoyannis, A.; Harissopulos, S.; Patronis, N. (HNPS Advances in Nuclear Physics, 2019)
N/A